2013
DOI: 10.1097/nmd.0b013e31827f64b0
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Disorder and Emotional Intelligence

Abstract: The present study investigated emotional intelligence (EI) in borderline personality disorder (BPD). It was hypothesized that patients with BPD (n = 61) compared with patients with other personality disorders (PDs; n = 69) and nonpatients (n = 248) would show higher scores on the ability to perceive emotions and impairments in the ability to regulate emotions. EI was assessed with the Mayer-Salovey-Caruso Emotional Intelligence Test (Mayer, Salovey, and Caruso [New York: MHS, 2002]). As compared with the PD gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
2
23
0
7
Order By: Relevance
“…According to various literatures, ASPD share ties with another common personality disorder named Borderline personality disorder (BPD). Peter and Colleagues (2013), EI among BPD individuals and they concluded that BPD is associated with emotion understanding deficits, whereas temporary severity of BPD is associated with emotion regulation deficits (Peter, Schuurmans, Vingerhoets, Smeets, Verkoeijen, & Arntz, 2013). Finally Copestake and Colleagues (2013), studied EI in psychopathy and their results somehow contradicted results of current study; they postulated that there was a negative relationship between self-report EI and ability EI.…”
Section: Discussionmentioning
confidence: 38%
“…According to various literatures, ASPD share ties with another common personality disorder named Borderline personality disorder (BPD). Peter and Colleagues (2013), EI among BPD individuals and they concluded that BPD is associated with emotion understanding deficits, whereas temporary severity of BPD is associated with emotion regulation deficits (Peter, Schuurmans, Vingerhoets, Smeets, Verkoeijen, & Arntz, 2013). Finally Copestake and Colleagues (2013), studied EI in psychopathy and their results somehow contradicted results of current study; they postulated that there was a negative relationship between self-report EI and ability EI.…”
Section: Discussionmentioning
confidence: 38%
“…Si bien es cierto que hasta hace poco no se ha empezado a hablar de inteligencia emocional y que aun son pocos los estudios que demuestran la relación entre presencia y gravedad del TLP con una baja IE. Parece que sería importante incluir ingredientes que fomentaran el desarrollo de la inteligencia emocional en el tratamiento de este trastorno (Gardner, Qualter & Tremblay, 2010;Lizeretti, Extremera & Rodrí-guez, 2012;Peter et al, 2013).…”
Section: Resultados De Efectividadunclassified
“…Por otra parte numerosos estudios sugieren que graves dificultades en la gestión emocional constituyen un aspecto nuclear en el TLP (Harned, Banawan & Lynch, 2006;Clarkin, Levy, Lenzenweger & Kernberg 2007;Gardner & Qualter, 2009;Gardner, Qualter & Tremblay, 2010;Peter et al, 2013). En esta línea, algunas investigaciones han demostrado que en el TLP se da una baja inteligencia emocional (IE), lo que supone una mala comprensión de las emociones propias y ajenas y un mal manejo de ellas (Gardner et al, 2010;Lizeretti, Extremera & Rodríguez, 2012;Peter et al, 2013).…”
unclassified
See 1 more Smart Citation
“…PC subjects (F[1,80] = 5.88, p = .018); Strategic EI did not differ as a function of these lifetime comorbid disorders. Finally, we added Borderline Personality Disorder (BPD) and Antisocial Personality Disorder (AsPD) to the ANOVA model because previous studies have reported lower EI scores among those with BPD Peter et al, 2013), or AsPD (Ermer et al, 2012), compared with controls. Including subjects with either BPD and/or AsPD did not affect the significance of the difference between PC and IED subjects (F[1,83] = 4.24, p = .043); Strategic EI did not differ as a function of BPD or AsPD.…”
Section: Resultsmentioning
confidence: 99%